Bivariate Extended Confluent Hypergeometric Function Distribution (2013)
ABSTRACT: In this article, we define a bivariate extended confluent hypergeometric function density in terms of extended confluent hypergeometric function. We also derive several of its properties and results in terms of extended beta, extended confluent hypergeometric, and modified Bessel functions.